STUDY OF LITERATURE ON CONCEPTS OF CULTURE AND EDUCATION - Desry Syahputra; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
Culture is all the work, taste, and creation of the community. Community work produces technology and material culture that are needed by humans to control the natural surroundings, so that their strengths and results can be devoted to the needs of society. Education means the process of changing the attitudes and behavior of a person or group of people in an effort to mature humans through teaching and training efforts, action processes, ways of educating. The role of education is as a transfer of cultural values or as the most effective way of transferring cultural values is by means of the educational process, because the two are very closely related. Culture and education are very closely related, both are mutually sustainable and cannot be separated because they are mutually and in need of each other.